Online question answering practices to support healthcare data re‐use. Issue 1 (2015) - Blake, Catherine; Souden, Maria; Anderson, Caryn L.; Twidale, Michael; Jenifer E., Stelmack
ABSTRACT: Institutional data collection practices inevitably evolve over time, especially in a distributed clinical setting. Clinical and administrative data can improve health and healthcare, but only if researchers ensure that the data is well‐aligned to their reuse goals and that they have adequately accounted for changes in data collection practices over time. Our goal is to understand information behaviors of health services data users as they bridge the gap between the historical data and their intended data reuse goals. This project leverages more than a decade of listserv posts related to the use of clinical and administrative data by US Department of Veterans Affairs (VA) employees, providing longitudinal insight into data reuse practices in both research and operational settings. In this paper we report the results of a pilot study that highlighted questions raised in the use of data and the knowledge engaged to answer them.